5, 6, 12, 13‐Tetraazaperopyrenes as Unique Photonic and Mechanochromic Fluorophores. (24th January 2020) - Yuan, Wei; Cheng, Junjie; Li, Xiaopei; Wu, Mengjiao; Han, Yi; Yan, Chunmei; Zou, Gang; Müllen, Klaus; Chen, Yulan
Abstract: 5, 6, 12, 13‐Tetraazaperopyrenes with different number of tert‐butyl groups (c‐TAPP‐T, c‐TAPP‐H) were synthesized, via four‐fold Bischler–Napieralski cyclization as the key step. As deduced from the single‐crystal structures and optical properties, N‐doping and substitution type allow for a precise control of intermolecular interactions. Compared to the reported 1, 3, 8, 10‐tetraazaperopyrenes, significantly different packing modes were found in 5, 6, 12, 13‐tetraazaperopyrenes. Going from c‐TAPP‐T to c‐TAPP‐H, two additional tert‐butyl groups lead to different preferential growth directions, affording 1D and 2D microcrystals, respectively. Most importantly, both microcrystals exhibit excellent optical waveguide properties with extraordinarily low loss coefficients and unique polarization features. Although c‐TAPP‐H possesses a rigid and planar core, its crystals display an exceptional mechanochromic fluorescence, which, again, depends on the mode of molecular packing. Abstract : Die regioselektive N‐Dotierung von Peropyrenen ermöglicht die maßgeschneiderte Herstellung von fluoreszierenden Mikrokristallen. 5, 6, 12, 13‐Tetraazaperopyren‐Derivate wurden synthetisiert, derenKristalle hervorragende Lichtwellenleitereigenschaften und eine außergewöhnliche mechanochrome Fluoreszenz aufweisen.